"Une Nègre de drame": Jane Vialle and the Politics of Representation in Colonial Reform, 1945–1953. (July 2020) - Dunstan, Sarah Claire
The French-Congolese Senator, Jane Vialle, was appointed as a French delegate to the United Nations in 1949. During her term she served on the Ad-Hoc Anti-Slavery committee as an expert on African colonial conditions and the status of African Women. Vialle's work on the international stage was an extension of her efforts towards reforming the political, social and economic rights of women at national and local levels, within the French Fourth Republic and the Oubangui-Chari region she represented in French West Africa. Despite her efforts, Vialle was frustrated with the glacial pace of reform in all three arenas, declaring to her friend and colleague, the African American historian and Pan-Africanist Rayford W. Logan, that she often felt she was being used as 'une nègre de drame'. Logan believed the expression was the French equivalent of the American phrase 'a showpiece or token negro'. Through the framework of Jane Vialle's political career, this articles explores how the notion of representation and what it meant to be 'une nègre de drame' or, indeed, to be an authentic representative of one's nation, race or gender intersected with Vialle's reformist efforts in Oubangui-Chari, the French Fourth Republic and on the international stage.